Ketidakpastian Global: Dampak Ekonomi dan Teknologi terhadap Ketahanan Pangan di Indonesia - Silalahi, Pristanto (Agric, 2025)
The Sustainable Development Goals (SDGs), as a common goal for all countries, place the issue of food security as one of the main targets of development in the world. In early 2019, the world faced COVID-19, affecting many aspects of human life, the economy, society, and above all, leading to a global food crisis. This article identifies and analyzes the effects of technology and economic recession on the food security crisis. The transformation of the Indonesian economy towards food security has recently become a major issue debated by many parties. The analysis method used in this study is a random effects model using panel data from all provinces in Indonesia from2019-2021 by using STATA software. Based on the data, the food security index is the dependent variable, while information and communication technology and gross regional domestic product are the independent variables. According to the results of the F-test (overall) conducted to test the significance of the model, these variables influence food security in Indonesia. Furthermore, this study’s results show that the economic recession’s impact is significant on food security. At the same time, technology has little impact on food security in Indonesia.